Characterization of Anthocyanin associated purple sweet potato starch and peel-based pH indicator films - Sohany, Mouluda; Mohamed Amin Tawakkal, Intan Syafinaz; Ariffin, Siti Hajar; Abdul Karim Shah, Nor Nadiah; Yusof, Yus Aniza (Multidisciplinary Digital Publishing Institute, 2021)
In food packaging, smart indicator films based on natural resources have greatly attracted researchers to minimize the environmental issues as well as to satisfy consumer preferences for food safety. In this research, pH-sensitive films were prepared using purple-fleshed sweet potato starch (SPS) and sweet potato peel (SPP). Two categories of the film (i) SPS and (ii) SPS/SPP, were fabricated via solvent casting technique, incorporating different concentrations of commercial purple sweet potato anthocyanin (CA) at 0%, 1%, 1.5%, and 2% (w/v) and the physicochemical, mechanical, thermal, and morphological properties of the films were investigated. The thickness, water solubility, and swelling degree of the films increased with the increment of CA, whereas there were no significant changes in the water content (WC) of the films. Water vapor permeability (WVP) was decreased for SPS films while statistically similar for SPS/SPP films. The addition of CA reduced the tensile strength (TS) and tensile modulus (TM) yet increased the elongation at break (EaB) of the films as compared to films without CA. The FTIR results confirmed the immobilization of anthocyanin into the film. In SEM images, roughness in the surfaces of the CA-associated films was observed. A reduction of thermal stability was found for the films with anthocyanin except for the SPS/SPP CA 2% film. Furthermore, the CA-associated films showed a remarkable color response when subjected to pH buffers (pH 1 to 12) and successfully monitored chicken freshness. The fastest color migration was observed in acidic conditions when the films were immersed into aqueous, acidic, low fat, and fatty food simulants. The findings of this work demonstrated that the developed pH indicator films have the potential to be implemented as smart packaging to monitor food freshness and quality for safe consumption.